Peran Kepala Sekolah Sebagai Supervisor Dalam Meningkatkan Kualitas Pembelajaran di MA Patra Mandiri Plaju Palembang - Febriyanti Febriyanti (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2017)
Supervision is an internal part of the education program, supervision is a cooperative service. Transcendental supervision is a series of activities in the context of supervision of the teaching profession. This research was conducted to reveal: 1) role of Principal as supervisor in improving learning quality. 2) supporting and inhibiting factors of the Principal's role as supervisor in improving the quality of learning. From the research result, the role of Principal as a supervisor in improving the quality of learning in Madrasah Aliayah Patra Mandiri Plaju has been done well but it needs to be improved again, the Principal has as much as possible in guiding, directing, designing, motivating to evaluate and maintain good relationship from inside school As well as from outside. While the inhibiting factors are, the principal is less experienced in supervising, lack of education operational support from the government and infrastructure facilities. While the supporting factor is, the willingness of teachers to receive guidance from the Principal Madrasah Aliyah Patra Mandiri Plaju, the participation of students who are active in school activities, the support of the superiors, and the existence of good relationships of school residents.